ANALISIS STRATEGI BERTAHAN PENGRAJIN ROTAN KOTA PEKANBARU - nofrizal nofrizal (Universitas Islam Nahdlatul Ulama Jepara, 2020)
The changing times have not changed rattan products, but they have been able to defense until now. This study aims to find out the factors that determine the defensive strategy of rattan craftsmen in Pekanbaru City. The object of the research was the rattan craftsmen in Pekanbaru City, totaling 42 business units. The data source was taken from primary and secondary data. The data collection techniques used interviews, questionnaires, and literature study. The variables in this study were categorized into two: external (opportunities and threats) and internal (strengths and weaknesses). The data analysis technique used descriptive quantitative technique. The variable measurement scale used four-point Likert Scale, from disagree to strongly agree. The results showed that the determinants of the rattan craftsmen to defense were price and reputation suitability with the average score of four, while the weak factors were the promotion form, quality of education, inflation development, CSR programs, and SME development programs with the average score of two.